Polynucleotides in Aesthetic Medicine: A Review of Current Practices and Perceived Effectiveness - Lee, Kar Wai Alvin; Chan, Kwin Wah Lisa; Lee, Angela; Lee, Cheuk Hung; Wan, Jovian; Wong, Sky; Yi, Kyu-Ho (International journal of molecular sciences, 2024)
Polynucleotides, complex molecules composed of nucleotides, have gained attention in aesthetic medicine for their potential to regulate gene expression and promote tissue regeneration. This review aims to provide an overview of the current practices and perceived effectiveness of polynucleotides in aesthetic medicine. A comprehensive search of the literature was conducted using keywords related to polynucleotides, cosmetic application, and aesthetic application. Studies were selected based on their relevance to aesthetic medicine and the inclusion of human subjects. The review found that polynucleotides have been used to improve skin texture, reduce wrinkle depth, and enhance facial appearance. The studies reported varying degrees of efficacy and safety, with some studies demonstrating significant improvements in skin elasticity and hydration. However, others reported limited or no benefits. The review also highlighted the need for further research to establish the optimal use and efficacy of polynucleotides in aesthetic medicine. While the existing literature suggests that polynucleotides may have potential benefits in aesthetic medicine, more research is needed to fully understand their mechanisms of action and optimal use. Clinicians should be aware of the current limitations and potential risks associated with the use of polynucleotides in aesthetic medicine.